Genetic analysis of environmental strains of the plant pathogen Phytophthora capsici reveals heterogeneous repertoire of effectors and possible effector evolution via genomic island - Iribarren, Maria Josefina; Pascuan, Cecilia Gabriela; Soto, Gabriela Cynthia; Ayub, Nicolás Daniel (Oxford University Press, 2021)
Phytophthora capsici is a virulent oomycete pathogen of many vegetable crops. Recently, it has been demonstrated that the recognition of the RXLR effector AVR3a1 of P. capsici (PcAVR3a1) triggers a hypersensitive response and plays a critical role in mediating non-host resistance. Here, we analyzed the occurrence of PcAVR3a1 in 57 isolates of P. capsici derived from globe squash, eggplant, tomato and bell pepper cocultivated in a small geographical area. The occurrence of PcAVR3a1 in environmental strains of P. capsici was confirmed by PCR in only 21 of these pathogen isolates. To understand the presence-absence pattern of PcAVR3a1 in environmental strains, the flanking region of this gene was sequenced. PcAVR3a1 was found within a genetic element that we named PcAVR3a1-GI (PcAVR3a1 genomic island). PcAVR3a1-GI was flanked by a 22-bp direct repeat, which is related to its site-specific recombination site. In addition to the PcAVR3a1 gene, PcAVR3a1-GI also encoded a phage integrase probably associated with the excision and integration of this mobile element. Exposure to plant induced the presence of an episomal circular intermediate of PcAVR3a1-GI, indicating that this mobile element is functional. Collectively, these findings provide evidence of PcAVR3a1 evolution via mobile elements in environmental strains of Phytophthora.